Determinan Status Imunisasi Dasar Pada Anak Balita 12-59 Bulan di Indonesia - Revita Virgini Mappadang; Fima F.L.G. Langi; Odi Roni Pinontoan (Sam Ratulangi Journal of Public Health, 2020)
Background: Immunization comes from the word "immune" meaning immunity. Immunization means being immunize, giving passive immunity (given antibodies) to the baby. The Indonesian Demographic Health Survey (IDHS) in 2017 shows that the achievement of complete basic immunization has not yet reached the government's target of 92%. This research aims to study the determinants of age of child, sex of child, age of mother, number of live children, level of mother’s education, residence and antenatal care with immunization. Method: This research was a quantitative with a cross sectional study design. The data used were secondary taken from 2017 IDHS data conducted in 34 provinces in Indonesia with a total sample of 9,424 children under five. Data were processed and analyzed in a univariate, bivariate, and multivariate manner using the chi square test. Result: highschool education (p= <0,001, AOR 0,757); number of children more than two (p=<0,001, AOR 0,728); and village residence (p=0,007, AOR 0,868) reduces odds ratio. Conclusion: the level of mother’s education, number of live children and residence are the determinants